Association between implantable cardioverter-defibrillator therapy and different lead positions in patients with cardiac resynchronization therapy. Issue 9 (27th September 2017) - Kronborg, Mads Brix; Johansen, Jens Brock; Haarbo, Jens; Riahi, Sam; Philbert, Berit Thornvig; Jørgensen, Ole Dan; Nielsen, Jens Cosedis
Abstract: Aims: To evaluate the impact of different right and left ventricular lead positions (RV-LP and LV-LP) on the risk of therapy for ventricular tachycardia/ventricular fibrillation in patients with a cardiac resynchronization therapy device (CRT-D). Methods and results: We performed a large nationwide cohort study on patients in Denmark receiving a CRT-D device from 2008 to 2012 from the Danish Pacemaker and implantable cardioverter defibrillator (ICD) registry. Lead positions were registered during the implantation and categorized as anterior/lateral/posterior and basal/mid-ventricular/apical for the LV-LP, and as apical/non-apical for the RV-LP. Appropriate and inappropriate therapies were registered during follow-up via remote monitoring or at device interrogations. Time to event was summarized with Kaplan–Meier plots, and competed risk regression analysis was used to calculate adjusted hazard ratios (aHR) with 95% confidence intervals (CI). Following variables were included in the analysis: gender, age, heart failure aetiology, New York heart association class, left ventricular ejection fraction, QRS duration, indication (secondary or primary prophylactic), RV-LP, LV-LP, and antiarrhythmic therapy. We included 1643 patients [mean age 68 (±10) years, 1343 (83%) men]. After a mean of 2.0 years, 322 (20%) patients received appropriate and 66 (4%) patients received inappropriate therapy. The aHR for appropriate therapy with a non-apical RV-LP was 0.70 95% CI (0.55–0.87, P  = 0.002) as compared with an apical. We observed no significant association between appropriate therapy and LV-LP in left anterior oblique or right anterior oblique views or inappropriate therapy between any lead positions. Conclusion: An apical RV-LP is associated with an increased risk of appropriate therapy for ventricular tachyarrhythmia in patients with a CRT-D device.